Characterization of Lignin Precipitated From The Soda Black Liquor of Oil Palm Empty Fruit Bunch Fibers by Various Mineral Acids - M.N Mohamad Ibrahim; S.B Chuah; W.D. Wan Rosli (ASEAN Journal on Science and Technology for Development, 2004)
Soda lignin from oil palm empty fruit bunch was directly isolated by various mineral acids i.e. sulfuric acid, hydrochloric acid, phosphoric acid and nitric acid at three levels of concentration (20% v/v, 60%v/v and concentrated). A comparison study was performed through physicochemical properties and structural features using FT-IR, UV, 13C-NMR and nitrobenzene oxidation. The FT-IR results showed that there is no significant difference between the main structures of the lignin isolated by various acids. However, low concentration of phosphoric acid is preferable because of its highest yield. The S: V: H ratio of 7-15:6-11:1 as evaluated by the nitrobenzene oxidation procedure suggests that soda lignin can be classified as belonging to either the cereal straw on grass type. The UV results indicate that phosphoric acid consistently gave the highest absorbance value among the four acids tested in this study regardless of its concentration level. The C13-FTNMR spectra, suggest that the lignin structure is independent of the type of acid used for precipitation.